Sex-dependent efficacy of sphingosine-1-phosphate receptor agonist FTY720 in mitigating Huntington’s disease - Jingyun Wu; Irene Santos-Garcia; Ivan Eiriz; Thomas Brüning; Aleš Kvasnička; David Friedecký; Tuula A. Nyman; Jens Pahnke (Pharmacological Research)
Huntington's disease (HD) is a debilitating neurodegenerative disorder characterized by severe motor deficits, cognitive decline and psychiatric disturbances. An early and significant morphological hallmark of HD is the activation of astrocytes triggered by mutant huntingtin, leading to the release of inflammatory mediators.Fingolimod (FTY), an FDA-approved sphingosine-1-phosphate (S1P) receptor agonist is used to treat multiple sclerosis (MS), a neuroinflammatory disease, and has shown therapeutic promise in other neurological conditions.Our study aimed to investigate the therapeutic potential of FTY for treating HD by utilizing a well-characterized mouse model of HD (zQ175dn) and wild-type littermates.The study design included a crossover, long-term oral treatment with 1 mg/kg to 2 mg/kg FTY from the age of 15–46 weeks (n = 128). Different motor behavior and physiological parameters were assessed throughout the study.The findings revealed that FTY rescued disease-related body weight loss in a sex-dependent manner, indicating its potential to regulate metabolic disturbances and to counteract neurodegenerative processes in HD. FTY intervention also rescued testicular atrophy, restored testis tissue structure in male mice suggesting a broader impact on peripheral tissues affected by huntingtin pathology. Histological analyses of the brain revealed delayed accumulation of activated astrocytes contributing to the preservation of the neural microenvironment by reducing neuroinflammation.The extent of FTY-related disease improvement was sex-dependent. Motor functions and body weight improved mostly in female mice with sustained estrogen levels, whereas males had to compensate for the ongoing, disease-related testis atrophy and the loss of androgen production.Our study underscores the beneficial therapeutic effects of FTY on HD involving endogenous steroid hormones and their important anabolic effects. It positions FTY as a promising candidate for therapeutic interventions targeting various aspects of HD pathology. Further studies are needed to fully evaluate its therapeutic potential in patients.